Krasa Bungah sebagai Inovasi pada Pengelolaan Sampah Berbasis Ekonomi Sirkular - Purwono, Purwono; Rahayu, Nur Laila (Universitas Teuku Umar, 2025)
The waste problem in Indonesia is becoming increasingly complex in line with the growth of the population and public consumption. The circular economy approach offers a sustainable alternative solution based on the principles of reducing, reusing, and recycling waste to maintain its economic value. This study examines a local, community-based innovation known as KRASA BUNGAH as a waste management model that integrates the concept of a circular economy. Waste management innovation that provides direct benefits to the community can serve as a solution by addressing waste at its source. The aim of this research is to evaluate the effectiveness of KRASA BUNGAH in supporting sustainable waste management. This study employs a descriptive method. The research sites were purposively selected in three locations. The study was conducted over eight months, with data collection carried out monthly. The results show that KRASA BUNGAH can serve as an innovative waste management model that promotes community self-reliance and is based on the principles of the circular economy.